Nestedness analysis as a tool to identify ecological gradients - Ulrich, Werner (Ecological Questions, 2009)
Nestedness describes patterns of species composition within continental biotas and among isolated habitats such as islands and landscape fragments. In a nested pattern, the species composition of small assemblages is an ordered subset (a true sample) of the species composition of large assemblages. Nested subsets of species are generated by environmental and ecological gradients, such as habitat quality, carrying capacities of sites, isolation, or fragmentation, that cause ordered sequences of species extinctions and colonization. Therefore nestedness analysis can be used to identify gradients that influence species composition and richness among sites and to identify species that run counter to these gradients (idiosyncratic species). Here I review the use of nestedness analysis to identify such gradients. I also describe how to perform the analysis and which metrics and null models to use for statistical inference.